Evaluation of Liver Enzymes in Normal Pregnancies in a University Hospital of Zabol Iran: A Cross-Sectional Study - Iraj Shahramian; Leli Rezaie Kahkhaie; Khadije Rezaie Keikhaie; Mahdi Shirdel Kahkha Zhaleh; Mahdi Afshari (Tehran University of Medical Sciences, 2023)
Objective: Changes in endocrine, nervous, renal, cardiovascular, and respiratory systems during pregnancy have been studied, but changes in liver function have been poorly studied. Therefore, the purpose of this study was to investigate the trend of changes in liver enzymes in normal pregnancy. Materials and methods: This prospective longitudinal study included 68 pregnant women who were referred to the Obstetrics and Gynecology Clinic of Amiral Momenin Hospital in Zabol in 2021. In terms of the trimester of pregnancy, the presence of underlying diseases, history of previous pregnancies, disorders of the enzymes of recent patients, the patients were evaluated, and the information from the patients' files was analyzed. Results: The average AST levels in pregnant women in the first, second, and third trimesters were 16.82, 17.47, and 18.00, respectively, which show that garlic consumption is increasing. The average PT in pregnant women decreased in the first, second, and third trimesters. The average direct and total bilirubin levels in pregnant women in the first and second trimesters showed a constant trend. The amount of total protein increased in pregnant women during the first, second, and third trimesters. In the second and third trimesters, the enzyme level was significantly higher in pregnant women than in nonpregnant women. The level of GGT in pregnant women in the first, second, and third trimesters showed a different trend. Conclusion: Accurate evaluation of patients, especially in the third trimester, is necessary from the point of view of increasing enzyme levels in other countries.